Identification Types of Plastic Waste Based On The Yolo Method - Saputro, Adi Kurniawan; Ulum, Miftachul; Khabibiy, Odiy Syahnurrokhim; Ibadillah, Achmad Fiqi; Alfita, Riza; Hardiwansyah, Muttaqin (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2024)
Plastic is still widely used in the daily lives of Indonesian people. As well as being an inexpensive material, plastic is characterized by weather, lightweight and corrosion resistance. In Indonesia, awareness of waste is still very low, resulting in the indiscriminate accumulation of garbage. Some people don't know the material from the type of plastic used These issues can be solved by using artificial intelligence advancements, such as computer vision.The yolov3 Tiny method was used to identify the type of plastic. The types of plastic used in this study were PET, PP, and HDPE. This method is implemented in a desktop-based application. The system is successful with an average accuracy value of 53.3%. The system easily recognizes the PET type, with an accuracy rating 70% greater than the other varieties. Whereas for the PP type, the result is 60% and for the HDPE type, it gets a value of 30%. For researchers, in turn, it may add a greater number of data slices and vary to be even more accurate in their identification.